Integrative systematic revision of the Montseny brook newt (Calotriton arnoldi), with the description of a new subspecies - Talavera, Adrián; Valbuena-Ureña, Emilio; Burriel-Carranza, Bernat; Mochales-Riaño, Gabriel; Adams, Dean C.; Amat, Fèlix; Carbonell, Francesc; Carranza, Salvador (PeerJ, 2024)
The Montseny brook newt (Calotriton arnoldi), a glacial relict endemic to a small, isolated massif in northeast Spain, is considered the only Critically Endangered urodele in Europe. Its restricted range is divided by a deep valley that acts as an impassable barrier to dispersal, separating two isolated metapopulations (Western and Eastern) that correspond to independent lineages with different evolutionary trajectories, based on genetic and genomic data. Here, we address the ecological differentiation between lineages and discuss its potential effect on the phenotypic distinctness of each lineage. Based on multiple lines of evidence, we formally describe the Western Montseny brook newt as a new subspecies: Calotriton arnoldi laietanus ssp. nov. Finally, our study underscores the importance of considering taxonomic progress in the conservation policies of endangered species, ensuring appropriate management and protection of the newly described taxa.
Keywords: Amphibians; Montseny brook newt; Calotriton arnoldi laietanus ssp. nov.; Morphology; Conservation; Subspecies